Headache-related cognitive distortions questionnaire - Vieira, Rebeca Veras de Andrade; Peterlin, B. Lee; Kowacs, Fernando; Londero, Renata Gomes; Barea, Liselotte Menke; Grassi, Vanise; Gomes, William Barbosa; Gauer, Gustavo (Headache Medicine, 2022)
Background. - Cognitive distortions are systematic errors in thinking and can be observed in the relationship of headache patients with their own disease and treatment.Objective. - To construct and validate an instrument to evaluate headache-related cognitive distortions in those with primary headache disorders; and to investigate the psychometric properties of this new instrument. Methods. - One hundred thirty-six (136) migraine outpatients from three Brazilian specialized headache hospital services completed the Headache-related Cognitive Distortions Inventory (HCDQ) and validated measures of psychological symptoms, pain catastrophizing, mood disorders, quality of life and headache-related disability. Results. - All hypothesized study measures’ correlations were statistically significant, supporting construct validity. HCDQ scores were positively correlated with headache frequency, headache intensity, psychological symptoms, depression, anxiety, and pain catastrophizing; and negatively correlated with 7 of 8 quality of life domains and time the patient was in treatment. Cronbach’s alpha demonstrated excellent internal consistency for the 17-item total scale (alpha=.92). Along with headache intensity and depression, HCDQ Pain subscale accounted for 46% of variance in the prediction of headache-related disability. Conclusions. - HCDQ is a valid and reliable measure of migraine patients´ cognitive distortions about their headaches and headache treatment.